2017
DOI: 10.1371/journal.pone.0170253
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Molecular Characteristics of Mycoplasma pneumoniae in Clinical Specimens from Children in Beijing between 2003 and 2015

Abstract: The molecular characteristics of 480 Mycoplasma pneumoniae polymerase chain reaction-positive specimens (331 were previously reported and 149 were newly reported) collected from pediatric patients in Beijing, China, between 2003 and 2015 were analyzed. Genotype M4-5-7-2/P1 were the most prevalent across the 13-year study period, although the isolation and mutation rates for this genotype varied between the periods 2003–2007, 2008–2013, and 2014–2015. In addition, there was a close association between the M4-5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 20 publications
11
36
0
Order By: Relevance
“…These observations suggest that changes in the proportion of MLVA types are due to a surge of type 3-5-6-2, which may have occurred worldwide except for in China. This and several previous studies demonstrated that most strains of MLVA type 3-5-6-2 were P1 type 2 or its variant, whereas MLVA type 4-5-7-2 was P1 type 1 (9,(11)(12)(13)21,30). Therefore, the increase in MLVA type 3-5-6-2 after 2011 may be a type-shift phenomenon of M. pneumoniae P1 types (7).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…These observations suggest that changes in the proportion of MLVA types are due to a surge of type 3-5-6-2, which may have occurred worldwide except for in China. This and several previous studies demonstrated that most strains of MLVA type 3-5-6-2 were P1 type 2 or its variant, whereas MLVA type 4-5-7-2 was P1 type 1 (9,(11)(12)(13)21,30). Therefore, the increase in MLVA type 3-5-6-2 after 2011 may be a type-shift phenomenon of M. pneumoniae P1 types (7).…”
Section: Discussionsupporting
confidence: 68%
“…The prevalence of MLVA type 3-5-6-2 was low: < 30 , in Yamagata, Japan (this study); China (9); the United States (20); and Australia (11) until 2010. However, after 2011, the prevalence of MLVA type 3-5-6-2 was > 30 in those countries (the present study, 11,20), Hong Kong (10), and Germany (21) except for China (9). These observations suggest that changes in the proportion of MLVA types are due to a surge of type 3-5-6-2, which may have occurred worldwide except for in China.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations